Clinical Diagnosis of an Autoimmune Encephalitis Presented as a Manic Episode with Psychotic Symptoms: A Case Report - Miguel Soto Ontoso; Ruben A. Piernas González; Isabel Ramírez Martínez; José Miguel Meca García (Case Reports in Psychiatry)
Introduction. Autoimmune encephalitis is caused by antineuronal immune mechanisms. Its clinical presentation is heterogeneous and in many cases onset with psychiatric symptoms. Paraclinical criteria guide the approach; however, the challenge occurs when there are no detectable autoantibodies in serum or cerebrospinal fluid (CSF). Methodology. We report one case that highlights the variability of clinical manifestations, which in the absence of antibodies was treated with immunotherapy with good response. Conclusion. In places where there is no antibody measurement, or when its measurement is negative, the clinical suspicion supported by CSF studies, magnetic resonance imaging, and electroencephalographic recording, should guide us to start immunotherapeutic treatment early. The early initiation of treatment ensures the reversibility of the neurological disorder in the vast majority of patients.